Obtaining infectious strains of Ustilago maydis for huitlacoche production in mexican rural society - Macuil Tlachino, Víctor; Sobal Cruz, Mercedes; Martínez Carrera, Daniel; Morales Almora, Porfirio; Peña Olvera, Benjamín; Maimone Celorio, María R. (Agricultura, Sociedad y Desarrollo, 2022)
Ustilago maydis is a dimorphic fungus with a non-pathogenic yeast-like form, and a pathogenic filamentous one that is responsible for the formation of tumors in maize. U. maydis is known in Mexico as huitlacoche and consumed since Pre-Hispanic times. Currently, its production is limited to collection in the wild for subsistence consumption and with assistance for market purposes, and for this reason it is necessary to have strains of U. maydis with a capacity for infection. In this study infectious sporidia were isolated from native huitlacoche from the Cholula region in Puebla, Mexico. The inoculum in liquid medium was prepared at a concentration of 1x106 and 5x106 sporidia mL-1; the concentration of the inoculum was measured in a UV spectrum with sporidia counts in Neubauer chamber. Six native sporidia were selected and crossed with two reference strains, CP-436 and CP-437, for the formation of infectious hybrids. The material selected was tested in vivo through the infection of maize seedlings of the variety HUE-CP-14. The native infectious strains were sporidia e7 and e11 of the strain CP-897, with formation of galls in the greenhouse at 7 days of maize seedling infection, and heterokaryons e7xCP-436, e7xCP-437, e11xCP-436, e11xCP-437, e14xCP-437, e7xe11, e14xe18 and CP-436xCP-437 as infectious hybrids at 14 days of inoculation on average.